2010
DOI: 10.1002/bdrc.20193
|View full text |Cite
|
Sign up to set email alerts
|

Adult hippocampal neurogenesis in aging and Alzheimer's disease

Abstract: Adult neurogenesis occurs in the subgranular zone of the hippocampal dentate gyrus and the subventricular zone of the lateral ventricles. This process is highly regulated by intrinsic and extrinsic factors, which may control the proliferation and/or maturation of neural progenitor cells. Adult-born neurons are integrated in preexisting networks and may have functional implications for adult brain. Here we attempt to summarize relevant findings concerning the physiological role of adult neurogenesis mainly focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 155 publications
3
28
0
Order By: Relevance
“…In addition, adult-born neurons are involved in certain aspects of hippocampus-dependent learning and memory, such as spatial memory, pattern separation and contextual fear conditioning [54,55]. A decrease in neurogenesis is a feature in the pathology of several neurological disorders [56,57]. Reminiscent of the altered levels of insulin in the MetS condition, it has been reported that insulin plays a central role in the formation of new neurons in the brain [58].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adult-born neurons are involved in certain aspects of hippocampus-dependent learning and memory, such as spatial memory, pattern separation and contextual fear conditioning [54,55]. A decrease in neurogenesis is a feature in the pathology of several neurological disorders [56,57]. Reminiscent of the altered levels of insulin in the MetS condition, it has been reported that insulin plays a central role in the formation of new neurons in the brain [58].…”
Section: Discussionmentioning
confidence: 99%
“…Such effects include an increase in the number of astrocytes and the amount of glial fibrillary acidic protein, reflecting gliosis in the aged brain (O'Callaghan and Miller 1991;Goss et al 1991;Bronson et al 1993;Linnemann and Skarsfelt 1994;Kohama et al 1995); a region-specific loss of neurons (Brody 1980;Devaney and Johnson 1980;Kiatipattanasakul et al 1996;Anglade et al 1997;Sjöbeck et al 1999;Smith et al 2004;Baskerville et al 2006); and an increase in the expression of proteins involved in the regulation of apoptotic cell death (Obonai et al 1998;Pañeda et al 2003). Another hallmark of gradual brain senescence is a dramatic agerelated decline in the generation of new neurons in the adult brain (for reviews see Galvan and Jin 2007;Jessberger and Gage 2008;Shruster et al 2010;Varela-Nallar et al 2010;Couillard-Despres et al 2011;Lee et al 2012).…”
Section: Introductionmentioning
confidence: 97%
“…Several studies have confirmed that the hippocampus shrinks with age (West 1993;Allen et al 2005;Greenberg et al 2008;Jernigan et al 2001;Mu et al 1999;Raz et al 2004;Scahill et al 2003;Schuff et al 1999;Walhovd et al 2005Walhovd et al , 2011. Further, evaluations of the hippocampus in humans have shown that the DG is indeed quite vulnerable to aging (Mueller et al 2008;Varela-Nallar et al 2010). Similarly, non-human primates (Gazzaley et al 1996;Small et al 2002Small et al , 2004 and rodents (Small et al 2004;Moreno et al 2007) have also shown the DG vulnerability to aging (Chawla and Barnes 2007;Varela-Nallar et al 2010).…”
Section: Aging: the Old Bag Of Tricksmentioning
confidence: 79%
“…Further, evaluations of the hippocampus in humans have shown that the DG is indeed quite vulnerable to aging (Mueller et al 2008;Varela-Nallar et al 2010). Similarly, non-human primates (Gazzaley et al 1996;Small et al 2002Small et al , 2004 and rodents (Small et al 2004;Moreno et al 2007) have also shown the DG vulnerability to aging (Chawla and Barnes 2007;Varela-Nallar et al 2010). A significant relationship exists between the development of AD and premorbid hippocampal volume.…”
Section: Aging: the Old Bag Of Tricksmentioning
confidence: 93%